Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/ajplung.00274.2014
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 restrains lung inflammasome activation in a murine model of sepsis

Abstract: Excessive inflammation is a major cause of organ damage during sepsis. The elderly are highly susceptible to sepsis-induced organ injury. Sirt1 expression is reduced during aging. In the present study, we investigated the role of Sirt1, a histone deacetylase, in controlling inflammatory responses in a murine sepsis model induced by cecal ligation and puncture (CLP). We examined lung inflammatory signaling in inducible Sirt1 knockout (Sirt1(-/-)) mice and wild-type littermates (Sirt1(+/+)) after CLP. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 63 publications
2
80
0
Order By: Relevance
“…However, the role of SIRT1 in sepsis is rarely studied and its exact mechanism is yet to be determined. Recently, a study showed that SIRT1 knockdown mice exhibited aggravated inflammatory signaling such as NF-kappa B in lung tissue of CLP mice [10]. Furthermore, pharmacological SIRT1 activation decreased mortality in experimental sepsis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of SIRT1 in sepsis is rarely studied and its exact mechanism is yet to be determined. Recently, a study showed that SIRT1 knockdown mice exhibited aggravated inflammatory signaling such as NF-kappa B in lung tissue of CLP mice [10]. Furthermore, pharmacological SIRT1 activation decreased mortality in experimental sepsis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Through deacetylation of histone and nonhistone substrate, SIRT1 is involved in various metabolic and inflammatory diseases [8, 9]. Interestingly, SIRT1 activity is decreased in the liver, spleen, small bowel, and lung tissue in experimental sepsis models, and SIRT1 activation could improve the outcome of sepsis and ameliorate the associated inflammatory response [10, 11]. Besides SIRT1, another sirtuin, SIRT3, has also received considerable attention [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The coverslips were mounted on the slides with DAPI. Immunoblotting assays of cell and lung tissue samples were conducted as described previously (15,16). Image analysis was carried out with the ImageJ program (v1.50i; National Institutes of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were terminated 24 h after LPS challenge. Lung wet/dry weight ratio was assessed as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…have demonstrated increased inflammasome activity in the lung of Sirt1-deficient mice compared to wild-type littermates after CLP. 40 The transcription activation of inflammasome components like NLRP3 can be regulated by active nf-kb which in turn is inhibited by Srt1 activation. 41,42 …”
Section: Discussionmentioning
confidence: 99%